(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article provides the results of eliminating scar deformities of the face and body using lipofilling. There were 2 groups of patients: the first group included 12 patients whose skin scars were localized within the dermis and did not affect the subcutaneous fat layer. Second group: 1 4 patients with atrophic scars of the skin and subcutaneous fat layer after injuries and surgical interventions. For the treatment of these patients, the method of autologous fat transplantation was chosen - lipofilling. Outcomes were assessed at 3 months and 9 months. The degree of survival of the autologous fat graft was assessed visually by the quality and type of scar deformities, as well as by ultrasound diagnostics by measuring the thickness of the subcutaneous fat layer over time. Treatment results were assessed according to clinical groups. Good and satisfactory results of surgical treatment, taking into account the additional exposure to high-intensity laser radiation, were observed in 7–2 % of patients in the first group. In the second group, good and satisfactory results were obtained in all patients.